Selling latrines to the poor: how effective it is? - Biswas, Sadhana; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
BRAC has been promoting personal hygiene practices and the use of safe water and sanitary latrines through its Rural Development Programme (RDP) since 1991. RDP sold a large number of latrines (45,000 as of June 1995) in it's operational areas (including Matlab) as part of a drive to improve rural sanitation through NGO forum. To study the impact of this on health as part of BRAC-ICDDR,B research framework in Matlab, it is important to understand how this programme is implemented. To provide feedback to the programme, this study aimed to explore the current status of the latrines sold by RDP in Matlab.